Estudo da curvatura residual aplicada ao problema da compressão dinâmica em risers rígidos em catenária livre - Amorim, Andre Ramiro (2018)
This work investigate the application of the residual curvature methodology to the TDP dynamic compression problem due to the FPSO excitation under extreme environmental loads. To do so, a load cases matrix is developed in order to evaluate geometrical parameters in order to control and forecast the phenomena. The results are presented, evaluated and compared to the rigid riser standard solution.